Personal Branding Rasyid Pada Media Sosial (Studi Akun Tiktok @rasyid1976) - Ikram, Syahruddin, Muslan (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
Social media has become a very effective tool in contemporary political communication. This phenomenon especially occurs in the current technological era, where it is increasingly easy to interact and get information through platforms such as TikTok, Facebook, Twitter, Instagram and YouTube. Politicians have realized that social media has tremendous power to expand the reach of political messages. They establish direct relationships with voters, and strengthen their image and reputation as leaders (Khaerunnisa, 2019). This research aims to understand the concept of forming personal branding through the TikTok application, by studying the TikTok account @rasyid1976. This research uses personal branding theory from Peter Montoya (2002) and descriptive qualitative research methods, with data collection techniques through observation, in-depth interviews and documentation. The research results show that the formation of personal branding on the TikTok account @rasyid1976 is demonstrated through eight theoretical indicators, namely: specialization, which reflects a humanist, humble and funny character; leadership, which shows attentiveness and seriousness; personality, which emphasizes simplicity; differences, which reflect the concept of simplicity in activities in society; visible, which shows a humorous character; unity, which emphasizes the importance of authenticity and consistency; steadfastness, which shows commitment and consistency in improving oneself; as well as a good name, which shows integrity and flexibility. This research concluded that the TikTok account @rasyid1976 succeeded in displaying a humanist, authentic and simple leadership concept, which succeeded in gaining widespread attention and support from the public.